DOI: 10.14264/uql.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein supplementation and plane of nutrition on the resistance and the resilience of Boer goats against artificial Haemonchus contortus infection under confined conditions

Abstract: The effects of protein and/ or energy supplementation have been well studied in sheep. However, the few pen studies conducted with goats have failed to identify the role of protein supplementation and combinations with energy supplements against H. contortus infection.The general objective of this thesis was to investigate the effects of protein supplementation and plane of nutrition on resistance and resilience of Boer goats to infection from Haemonchus contortus. To achieve this the first experiment was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 281 publications
(547 reference statements)
0
1
0
Order By: Relevance
“…In addition, because the degree of infectivity varies significantly according to the H. contortus isolates, studies concluded on the importance to take in to account the parasite genetic diversity in various agro-ecological zones (Aumont et al, 2003) in all prevention and control measures. These above factors justify its high pathogenicity which is a requirement to the treatment and control of this parasite in small ruminants (Can, 2015) *Corresponding author e-mail: abiodouno@yahoo.fr. Tel: +229 97 085 468.…”
Section: Morphology and Biological Characteristics Of H Contortusmentioning
confidence: 99%
“…In addition, because the degree of infectivity varies significantly according to the H. contortus isolates, studies concluded on the importance to take in to account the parasite genetic diversity in various agro-ecological zones (Aumont et al, 2003) in all prevention and control measures. These above factors justify its high pathogenicity which is a requirement to the treatment and control of this parasite in small ruminants (Can, 2015) *Corresponding author e-mail: abiodouno@yahoo.fr. Tel: +229 97 085 468.…”
Section: Morphology and Biological Characteristics Of H Contortusmentioning
confidence: 99%